2007
DOI: 10.1016/j.jacc.2007.01.093
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention in Patients Receiving Enoxaparin or Unfractionated Heparin After Fibrinolytic Therapy for ST-Segment Elevation Myocardial Infarction in the ExTRACT-TIMI 25 Trial

Abstract: Among patients treated with fibrinolytic therapy for STEMI who underwent subsequent PCI, ENOX administration was associated with a reduced risk of death or recurrent MI without difference in the risk of major bleeding. The strategy of ENOX support for fibrinolytic therapy followed by PCI is superior to UFH and provides a seamless transition from the medical management to the interventional management phase of STEMI without the need for introducing a second anticoagulant in the cardiac catheterization laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 17 publications
0
65
0
1
Order By: Relevance
“…6,7,70,76,77 When moving to PCI after fibrinolytic therapy, those patients who received upstream UFH or enoxaparin can continue to receive those anticoagulants in a seamless fashion (i.e., without crossover to another agent) using the dosing regimens listed in the recommendations. 73 On the basis of the reports of catheter thrombosis with fondaparinux alone during primary PCI in OASIS-6 and the experience with fondaparinux in the OASIS-5 trial, 78 the writing group thought fondaparinux should not be used as the sole anticoagulant during PCI but should be coupled with an additional agent that has anti-IIa activity to ameliorate the risk of catheter complications. Although bivalirudin and UFH are potential options for supplemental anticoagulation with fondaparinux, the available experience, albeit limited, is largely with UFH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,70,76,77 When moving to PCI after fibrinolytic therapy, those patients who received upstream UFH or enoxaparin can continue to receive those anticoagulants in a seamless fashion (i.e., without crossover to another agent) using the dosing regimens listed in the recommendations. 73 On the basis of the reports of catheter thrombosis with fondaparinux alone during primary PCI in OASIS-6 and the experience with fondaparinux in the OASIS-5 trial, 78 the writing group thought fondaparinux should not be used as the sole anticoagulant during PCI but should be coupled with an additional agent that has anti-IIa activity to ameliorate the risk of catheter complications. Although bivalirudin and UFH are potential options for supplemental anticoagulation with fondaparinux, the available experience, albeit limited, is largely with UFH.…”
Section: Resultsmentioning
confidence: 99%
“…UFH was dosed according to the activated clotting time (ACT), using a target of 200 seconds for patients receiving a GP IIb/IIIa inhibitor and 250 seconds for those not receiving a GP IIb/IIIa inhibitor. 73 The main observations (Table 9) were the same whether the results were analyzed by intention to treat or by the actual anticoagulant received during the procedure (blinded study or open-label anticoagulant if PCI was performed after Day 8). 73 …”
Section: Ancillary Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with STEMI to be treated with fibrinolysis, 17 studies supported enoxaparin over UFH (LOE1 336,[387][388][389][390][391][392][393] ; LOE 2 341,394,395,396 ; LOE 4 397 ; LOE 5 393,396,398 -401 ) Twelve other studies were neutral comparing enoxaparin and UFH. [402][403][404][405][406][407][408][409][410][411] Reviparin.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…96 The Enoxaparin and Thrombolysis Reperfusion for Acute Myocardial Infarction Treatment (EXTRACT-TIMI 25) trial demonstrated reduced rates of reinfarction with the low-molecular-weight heparin enoxaparin compared with unfractionated heparin in patients receiving fibrinolytic therapy and in those undergoing PCI after fibrinolysis. 97,98 This agent has not been meaningfully studied in the primary PCI setting, however. The selective factor Xa inhibitor fondaparinux was randomized against unfractionated heparin in 3788 patients undergoing primary PCI in the placebo-controlled, double-blind Organization to Assess Strategies for Ischemic Syndromes (OASIS-6) trial.…”
Section: Adjunctive Antiplatelet and Antithrombin Pharmacologymentioning
confidence: 99%